Business Information Culture - Gunilla Widén-Wulff (Information Research: An International Electronic Journal)
This research project is going to review the existing information cultures in 15 Finnish insurance businesses through a qualitative study. The interview-material consists of 40 in-depth-interviews and they are being analysed through the multiple case study method. The analysis is conducted in 5 stages considering information environment, information as resource, work processes, innovation and business success. The information culture varieties compared to the business success will hopefully be useful to create an understanding for the need of a broad understanding of the modern knowledge management concept in business organisations.